Synthesis, biophysical characterization, and anti-HIV-1 fusion activity of DNA helix-based inhibitors with a p-benzyloxyphenyl substituent at the 5′-nucleobase site. Issue 10 (1st June 2018) - Tang, Yongjia; Han, Zeye; Guo, Jiamei; Tian, Yangli; Liu, Keliang; Xu, Liang
Graphical abstract: Highlights: Two new nucleoside analogues and four DNA helix-based inhibitors were synthesized. All the helix-based molecules showed anti-HIV-1 fusion activity. The p -benzyloxyphenyl group and attached linker affect the helix thermal stability. Inhibitors with same DNA helix may have variable reaction targets. Abstract: DNA helix-based HIV-1 fusion inhibitors have been discovered as potent drug candidates. Introduction of hydrophobic groups to a nucleobase provides an opportunity to design inhibitors with novel structures and mechanisms of action. In this work, two novel nucleoside analogues (1 and 2 ) were synthesized and incorporated into four DNA duplex- and quadruplex-based inhibitors. All the molecules showed anti-HIV-1 fusion activity. The effect of the p -benzyloxyphenyl group and the attached linker on the helix formation and thermal stability were fully compared and discussed. Surface plasmon resonance analysis further indicated that inhibitors with the same DNA helix may still have variable reaction targets, mainly attributed to the different hydrophobic modifications.